Contractile Activity Is Necessary to Trigger Intermittent Hypobaric Hypoxia-Induced Fiber Size and Vascular Adaptations in Skeletal Muscle - Rizo-Roca, David; Bonet, Jèssica B.; Ínal, Büsra; Ríos-Kristjánsson, Juan Gabriel; Pagès, Teresa; Viscor, Ginés; Torrella, Joan R. (Frontiers in Physiology, 2018)
Altitude training has become increasingly popular in recent decades. Its central and peripheral effects are well-described; however, few studies have analysed the effects of intermittent hypobaric hypoxia (IHH) alone on skeletal muscle morphofunctionality. Here, we studied the effects of IHH on different myofibre morphofunctional parameters, investigating whether contractile activity is required to elicit hypoxia-induced adaptations in trained rats. Eighteen male Sprague-Dawley rats were trained one month and then divided into three groups: (1) rats in normobaria (trained normobaric inactive, TNI); (2) rats subjected daily to a 4-hour exposure to hypobaric hypoxia equivalent to 4,000 m (trained hypobaric inactive, THI); and (3) rats subjected daily to a 4-hour exposure to hypobaric hypoxia just before performing light exercise (trained hypobaric active, THA). After two weeks, the tibialis anterior muscle (TA) was excised. Muscle cross-sections were stained for: (1) succinate dehydrogenase to identify oxidative metabolism; (2) myosin-ATPase to identify slow- and fast-twitch fibres; and (3) endothelial-ATPase to stain capillaries. Fibres were classified as slow oxidative (SO), fast oxidative glycolytic (FOG), fast intermediate glycolytic (FIG) or fast glycolytic (FG) and the following parameters were measured: fibre cross-sectional area (FCSA), number of capillaries per fibre (NCF), NCF per 1,000 µm2 of FCSA (CCA), fibre and capillary density (FD and CD), and the ratio between CD and FD (C/F). THI rats did not exhibit significant changes in most of the parameters, while THA animals showed reduced fibre size. Compared to TNI rats, FOG fibres from the lateral/medial fields, as well as FIG and FG fibres from the lateral region, had smaller FCSA in THA rats. Moreover, THA rats had increased NCF in FG fibres from all fields, in medial and posterior FIG fibres and in posterior FOG fibres. All fibre types from the three analysed regions (except the posterior FG fibres) displayed a significantly increased CCA ratio compared to TNI rats. Global capillarisation was also increased in lateral and medial fields. Our results show that IHH alone does not induce alterations in the TA muscle. The inclusion of exercise immediately after the tested hypoxic conditions is enough to trigger a morphofunctional response that improves muscle capillarisation.